Ni, Co, Zn, and Cu metal-organic framework-based nanomaterials for electrochemical reduction of CO2: A review - Do, Ha Huu; Truong, Hai Bang (Beilstein Journal of Nanotechnology, 2023)
The combustion of fossil fuels has resulted in the amplification of the greenhouse effect, primarily through the release of a substantial quantity of carbon dioxide into the atmosphere. The imperative pursuit of converting CO2 into valuable chemicals through electrochemical techniques has garnered significant attention. Metal-organic frameworks (MOFs) have occured as highly prospective materials for the reduction of CO2, owing to their exceptional attributes including extensive surface area, customizable architectures, pronounced porosity, abundant active sites, and well-distributed metallic nodes. This article commences by elucidating the mechanistic aspects of CO2 reduction, followed by a comprehensive exploration of diverse materials encompassing MOFs based on nickel, cobalt, zinc, and copper for efficient CO2 conversion. Finally, a meticulous discourse encompasses the challenges encountered and the prospects envisioned for the advancement of MOF-based nanomaterials in the realm of electrochemical reduction of CO2.
Keywords: carbon capture; CO2 reduction; electrocatalysis; metal-organic frameworks; nanomaterials